Reshaping heavy rare earth supply chains amidst China's stringent environmental regulations - Wei Chen; Peng Wang; Fanran Meng; Alexandra Pehlken; Qiao-Chu Wang; Wei-Qiang Chen (Fundamental Research)
China's official heavy rare earths (HREs) supply, vital to the global sustainable transition, has declined by 90% over the past 20 years. Global concerns have mounted regarding China's production quota policies, yet the real-world bottlenecks remain unclear. This study explores China's terbium (a critical HREs element) supply-demand conflicts and supply chain bottlenecks, and further simulates future potential changes. We identify a growing terbium shortage (a total of 3300 metric tons) in China as its registered production declined by 90% during the period from 2007 to 2018. Contrary to previous views that attribute HREs supply limitations to the production quota policy, we find that only 25% of China's quota related to HREs was utilized in 2018. Such a large quota-supply gap stems primarily from the enforced closures of HREs mines since the current mining techniques failed to reach strict environmental regulations. Furthermore, our simulations predict a 2–5-fold increase in terbium shortage by 2060 under the burgeoning ambitions in electric vehicles and wind power. However, this looming shortage could potentially be mitigated by 27%–70% under the scenario of breakthroughs in green mining techniques. This study highlights the urgency of seeking and promoting HREs green mining technologies, with implications for shifting global attention from geopolitical competition to green supply of rare earth and other minerals.